2018
DOI: 10.14260/jemds/2018/155
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Properties in Bark and Leaf Extracts of Four Cinnamomum Species

Abstract: BACKGROUND Cinnamon has been recognised for its flavouring and medicinal properties since ancient times and is the second most important spice sold in the world market. The antibacterial activities of hexane, chloroform, methanol and water extracts of four Cinnamomum species were studied. MATERIALS AND METHODSBoth bark and leaf extracts of C. verum, C. cassia, C. tamala and C. camphora was tested in vitro against 12 bacterial species by agar well diffusion assay and minimum inhibitory concentration (MIC) was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…Cinnamon bark oil -1 12.5, 25, and 50 mg ml caused cell death as evidenced by lack of growth across all isolates after 24 hr of incubation (Fig. 7), a finding that is consistent with those of previous studies (Abdel-Moaty et al, 2016;Keloth et al, 2018). These impacts are ascribed to the lipophilic nature and low molecular weight of important elements consisting of essential oils that enable them to cross cell membranes, change membrane structure, and boost membrane fluidity, resulting in ion leakage and cytoplasmic molecules.…”
Section: Ms Abdel-hamid Et Al: Essential Oils As Antimicrobialssupporting
confidence: 92%
See 2 more Smart Citations
“…Cinnamon bark oil -1 12.5, 25, and 50 mg ml caused cell death as evidenced by lack of growth across all isolates after 24 hr of incubation (Fig. 7), a finding that is consistent with those of previous studies (Abdel-Moaty et al, 2016;Keloth et al, 2018). These impacts are ascribed to the lipophilic nature and low molecular weight of important elements consisting of essential oils that enable them to cross cell membranes, change membrane structure, and boost membrane fluidity, resulting in ion leakage and cytoplasmic molecules.…”
Section: Ms Abdel-hamid Et Al: Essential Oils As Antimicrobialssupporting
confidence: 92%
“…These results corroborates with the previous study of Trajano et al (2010) who reported that the essential oil of Cinnamon zeylanicum as an alternative source of antimicrobial compound was effective against Staphylococcus aureus in food protection systems. Cinnamon bark oil is the most potent essential oil Sütterlin et al, ( against bacterial ESBL strains.The results we obtained for E. coli EMH-542017 in the time-kill assay following the cinnamon bark oil treatment is in line with those of Keloth et al (2018), who confirmed that cinnamon bark oil has a remarkable potential to inhibit the growth of E. coli strains with ESBLs in UTIs.…”
Section: Ms Abdel-hamid Et Al: Essential Oils As Antimicrobialssupporting
confidence: 89%
See 1 more Smart Citation